Long-Term Effect of Tillage Practices and Nitrogen Fertilization on Corn Yield - Carlos A. Bonini Pires; Marcos M. Sarto; James S. Lin; William G. Davis; Charles Rice (Kansas Agricultural Experiment Station Research Reports, 2020)
The objective of this study was to investigate the effect of different tillage systems and nitrogen (N) fertilizers on corn yield. Higher corn yields (207 bu/a and 203 bu/a) were found under no-tillage + high (150 lb N/a) manure application, and tillage + super high manure (750 lb N/a), respectively. The trend observed for the different nitrogen fertilizers between tillage systems was the same. However, a greater corn yield was observed under no-till in comparison to tilled conditions for both high fertilizer and high manure. No-till improves soil water infiltration, aggregation, nutrient cycling, and may increase crop yield. On other hand, soil erosion, runoff, and a depreciated plant stand may have been the reasons for lower yields under tillage for some of the treatments. Overall, the addition of organic fertilizer associated with no-till was a better practice for increasing corn yield compared to the use of mineral fertilizer associated with or without tillage.
Keywords: no-till; organic fertilizer; mineral fertilizer